Theoretical and Methodological Provisions of Quality Management of Professional Activity of The Teaching Staff of Higher Educational Institutions - Y. V. Razumova; E. M. Trapeznikova (Ekonomika Nauki)
The article substantiates the relevance of assessing the quality of professional activity of the teaching staff of higher educational institutions in the context of the transformation of the educational process. A study of theoretical and methodological aspects of assessing the quality of work of teaching staff has been conducted. The key components of the category “quality of professional activity of the teaching staff” are identified and a definition based on the essential aspects of the selected components is formulated. The main trends characterizing the modern system of higher education (elements of the transformation of the higher education system) are also highlighted, their impact on the activities of teaching staff of higher educational institutions is analyzed and the emerging demands of the external environment for the qualification of teaching staff are highlighted. As a result of the study, the authors identified inconsistencies in the theoretical and methodological provisions of the assessment of the quality of teaching staff, in particular, inconsistencies between the normative and actual qualification and competence requirements for teaching staff in the conditions of transformation of the educational system.